Didrichsen Art Museum : Catalogue. - collectie Didrichsen Art Museum Helsinki (Helsinki : Didrichsen Art Museum)
Aalto, Ilmari ; Ahlgren, Lauri ; Cawén, Alvar ; Collin, Marcus ; Colliander, Ina ; Dahlman, Helge ; Edelfelt, Albert ; Ekelund, Ragnar ; Enckeli, Magnus ; Enboth, Erik ; Eteläniemi, Osmo ; Favén, Mauri ; Finch, A.W. ; Albers, Josef ; Dali, Salvador ; Delaunay, Sonia ; Kandinsky, Wassily ; Léger, Fernand ; Miró, Joan ; Poliakoff, Serge ; etc.
boek